The Poet as a Saint: The Caxton Master’s Portrait of Ovid and Its Literary Background - Hollick, Bernhard (Actual Problems of Theory and History of Art, 2015)
The frontispiece of William Caxton’s Middle English translation of the Ovide moralisé en prose in Cambridge, Magdalen College, Old Library, Ms. F.4.34, fol. 16r, shows Ovid as a Christian saint, praying to and receiving inspiration from an image of Christ. There is no similar picture in any other manuscript. However, the artist, who is usually referred to as the Caxton Master, could draw on a broad literary background: the text illustrated by him belongs to a group of sources from France, which offer Christian interpretations (the so-called moralisations) of the Metamorphoses. At the same time, the Caxton Master is rooted in a home-grown English classicism, which from 1300 onwards established Ovid as a major authority, as is evident by commentaries, sermons, and — most surprisingly — scholastics writings. This paper aims to shed light on this interaction of literature and art.
Keywords: Bersuire; Bradwardine; Caxton; frontispiece; Ovid; Ovide moralisé; portrait; Walsingham